The Wealth Effects of Bank Financing Announcements in Highly Leveraged Transactions. - Kracaw, William A; Zenner, Marc (Journal of Finance, 1996)
The authors analyze the effect of financing announcements of highly leveraged transactions on the stock prices of the banks that lead highly leveraged transaction lending syndicates. For their sample of forty-one highly leveraged transactions, the authors document that the first highly leveraged transaction and bank financing announcements result in positive wealth effects for the lending banks. They also find that these wealth effects are lower in 1985, for smaller highly leveraged transactions, and for banks with a high loan loss reserve to total asset ratio. Finally, they report that leveraged buyout targets gain about 2 percent, whereas leveraged recap targets lose about 2 percent, when the first bank financing agreement is announced.